Reply to Before scoliosis can be attributed to the variant c.326G>A in MYH3, its pathogenicity must be proven - Maria Chiara Maccarone; Matilde Paramento; Edoardo Passarotto; Paola Contessa; Maria Rubega; Emanuela Formaggio; Stefano Masiero (European Journal of Translational Myology, 2025)
Dear Editor,